2023
DOI: 10.1094/pdis-04-22-0728-sr
|View full text |Cite
|
Sign up to set email alerts
|

Aggressivity of Different Fusarium Species Causing Fruit Rot in Melons in Brazil

Abstract: Brazil is one of the largest melon (Cucumis melo) producers in the world and most of the production is exported to international markets. Currently, over 15% of the Brazilian melon shipments are lost during export transportation due to Fusarium fruit rot, which is jeopardizing the livelihood of the Brazilian melon producers. Herein, we focused on understanding the aggressivity of five different species of Fusarium causing fruit rot on the main types of melon produced in Brazil. We also investigated the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The fungal diseases of plants in the family Cucurbitaceae mainly include Phytophthora blight caused by Phytophthora capsici, powdery mildew caused by Podosphaera xanthii, and Fusarium diseases caused by Fusarium species [19,20]. Fusarium fruit rot is an important disease affecting melons and pumpkins, which leads to economic and quality losses [6,10]. Recent studies revealed F. asiaticum and F. incarnatum, as novel pathogens, can cause fruit rot on melons in China [7,21,22], while F. solani f. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal diseases of plants in the family Cucurbitaceae mainly include Phytophthora blight caused by Phytophthora capsici, powdery mildew caused by Podosphaera xanthii, and Fusarium diseases caused by Fusarium species [19,20]. Fusarium fruit rot is an important disease affecting melons and pumpkins, which leads to economic and quality losses [6,10]. Recent studies revealed F. asiaticum and F. incarnatum, as novel pathogens, can cause fruit rot on melons in China [7,21,22], while F. solani f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…melonis (Fom), which determined the difference in host range compared with F. oxysoporum f. sp. radiciscucumerinum (Forc) [9]; and the pathogenicity of five species of Fusarium (Fusarium sp., F. sulawesiense, F. falciforme, F. kalimantanense, and F. pernambucanum) and their effects on melon fruit quality in Brazil [10].…”
Section: Introductionmentioning
confidence: 99%
“…All isolates were identified by Medeiros Araújo et al (2021) using molecular techniques and are deposited in the Coleção Micológica de Lavras (CML) at the Universidade Federal de Lavras, Minas Gerais, Brazil. These isolates were previously selected after pathogenicity test by Nogueira et al (2023), confirming their high level of aggressiveness. The culturing of all isolates was performed in Petri dishes with potato dextrose agar medium (PDA; Merck KGaA).…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…It is estimated that approximately 15% of exported melons reach the importing market with symptoms of post-harvest diseases, causing severe losses to producers, as it renders them unfeasible for commercial use (Oster et al, 2018). Among the post-harvest diseases in melon, fruit rot caused by fungi belonging to the genus Fusarium stands out (Li et al, 2019;Nogueira et al, 2023). Fusarium rot in melon has been observed since 1999, with the causal agent initially identified as Fusarium pallidoroseum (synonyms: F. incarnatum, F. semitectum) (Huang et al, 2000).…”
mentioning
confidence: 99%
“…Studies have shown that postharvest pathogenic fungal colonies of melons are diverse, with Fusarium being the dominant fungal genus ( Zheng et al, 2020 ). More than 15% of Brazilian melons are reportedly lost to Fusarium fruit rot during export transport ( Nogueira et al, 2023 ). Fusarium is an important postharvest pathogen of fruits and vegetables and can infect fruits and vegetables such as blackthorn plum ( Hye, Thi & Hyang, 2016 ), watermelon ( Balasubramaniam et al, 2023 ), winter pumpkin ( Kitabayashi et al, 2023 ), banana ( Kanhe, Abhilasha & Girish, 2019 ), pineapple ( Barral et al, 2019 ), kiwifruit ( Wang et al, 2023 ) and melon ( Nogueira et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%